Small religious group in the urban environment: failure of the Bahá’i project - Ryazanova, Svetlana V. (Journal of the Belarusian State University. Sociology, 2021)
The article is devoted to the study of the proselytising strategy of the Bahá’i community in the Perm Territory that reflects the situation with this religious group in the Russian Federation as a whole. Bahá’i s are seen as one of the new religious projects of the end of the last century, claiming a wide coverage of believers and being unable to fulfill the task. The main research question is to identify obstacles for effective proselytising activities of new religious movements as features of the religious groups. The aim of the work is to identify effective mechanisms for recruiting neophytes in the urban environment, which involves channels for transmitting teachings, main factors of the proselytic potential of religion, the connection between doctrine, cult practice and the success of the missionary activity. The article presents the first experience of a sociological analysis of the regional Bahá’i community as a new religious movement in the post-Soviet space. The study is built on a set of included observations, results from a survey of church members, a series of semi-structured interviews, an analysis of sacred literature and information from social networks. Particular attention is paid to the specifics of the spread of the Bahá’i faith in the country and the social characteristics of the neophytes. The main types of religious and near-religious activities of the community and ways of attracting new followers are analysed. The reasons and factors of the curtailment of activity and decline of the community, as well as the chosen development tactics at the present stage, are identified. The Bahá’i community is treated as uncompetitive in the religious space of the region and country. This is determined by the high value of the individual qualities of the followers, a low degree of external attractiveness, and poor adaptation to the religious needs of the population. The analysis of the community allows us to establish the place of new religious movements in the social and cultural space and the prospects for their development as local communities.